A study to assess awareness regarding eye donation among post graduate medical students admitted through NEET pre PG 2014 of Gajra Raja medical college Gwalior, M.P., India - Tiwari, Ranjana; Rajput, Ajit Singh; Jain, Vikas; Goyal, Manish; Mahore, Rakesh; Tiwari, Sakshi (International Journal of Research in Medical Sciences, 2017)
Background: According to WHO estimates India has 10 million blind populations. Corneal problems cause a significant proportion of blindness in India. Although effective strategies to prevent corneal blindness are likely to be more cost effective, visual rehabilitation by corneal transplantation remains the major treatment for restoring sight in those who already have corneal blindness. The requirement of donor corneas per year is at least 20 times the current procurement. Objective: To assess the knowledge and attitude of post graduate medical students regarding eye donation and their willingness to pledge eyes for donation. Methods: The present study was a cross sectional study conducted using a pretested questionnaire on 116 Post graduate Medical Students but only 106 actually participated in the study. Results: A total of 106 students actually participated in the study. Among them 63 (59.43%) were males and 43 (40.57%) were females. The maximum percentages of the students were of age group 26-29 years. All the students were aware regarding eye donation but still they felt it was necessary to obtain consent from family members. Conclusion: These data showed that although the awareness is good but still there is imperative need to emphasize to evade myths concerning eye donation to promote eye donation.